2016
DOI: 10.1002/j.0022-0337.2016.80.10.tb06199.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Dental School's Clinic Operations Using Lean Process Improvement

Abstract: The term "lean production," also known as "Lean," describes a process of operations management pioneered at the Toyota Motor Company that contributed significantly to the success of the company. Although developed by Toyota, the Lean process has been implemented at many other organizations, including those in health care, and should be considered by dental schools in evaluating their clinical operations. Lean combines engineering principles with operations management and improvement tools to optimize business … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 3 publications
0
21
0
4
Order By: Relevance
“…‐ 16 Process improvement principles have long been used in business environments to improve efficiency and enhance quality 17 , 18 . They are now being implemented in public services, dental education, and the delivery of oral health care 15 , 16 , 19 . While lean management is becoming a trend of research in the health care arena, recent reviews of the health care literature from 2000 to 2015 found that only 45‐51% of the studies used lean techniques to enhance operational performance 19…”
Section: Methodsmentioning
confidence: 99%
“…‐ 16 Process improvement principles have long been used in business environments to improve efficiency and enhance quality 17 , 18 . They are now being implemented in public services, dental education, and the delivery of oral health care 15 , 16 , 19 . While lean management is becoming a trend of research in the health care arena, recent reviews of the health care literature from 2000 to 2015 found that only 45‐51% of the studies used lean techniques to enhance operational performance 19…”
Section: Methodsmentioning
confidence: 99%
“…A study at the University of Kentucky School of Dentistry evaluated patient satisfaction when appointment length in the emergency clinic was reduced from four hours to three hours using Lean processes 1 . Reducing the length of the appointment may also enable care to be delivered to more patients; however, that factor was not measured or reported in that study.…”
mentioning
confidence: 99%
“…This difference may mean that improving efficiency could have very different meanings and pathways at different dental schools. There is very little research on efficiency in dental school clinics other than the Kentucky and Harvard studies 1, 2 . When the scope is broadened to consider process automation in dentistry, one study focused on laboratory processes (rather than clinical processes) found that error rates and patient safety improved 6 .…”
mentioning
confidence: 99%
“…In 2007, Teresko noted that Toyota's innovation was driven by the company's “commitment to ‘the importance of appropriately integrating people, processes, tools, and technology to add value to the customer and society,’” in the words of the authors of a book on TPS 1 . At that time, Teresko emphasized that successful companies had learned that “less of [their] edge now comes from TPS and more comes from adopting lean product development practice” in combination with “dedication to continuous improvement.” In dental education, academic dental institutions have used these processes to improve management of the dental clinic and to streamline overall dental school operations 2 , 3 . Introduction of lean product development in all these areas has been greatly facilitated by innovations of the digital age.…”
mentioning
confidence: 99%